Application of the Delphi method for the analysis of the factors determining social entrepreneurship - García-Uceda, Esperanza (2017)
This paper presents an exploratory analysis of the factors determining the choice of social entrepreneurship (SE) as a business model. Attention is focused on the motivations for choosing this entrepreneurship alternative and on the difficulties that the people embarking on this venture encounter. After applying the Delphi method and with the collaboration of a panel of experts formed by 20 specialists in social entrepreneurship, we can conclude that the most important motivations are the social entrepreneur?s self-fulfillment, self-esteem and passion for social issues. The main obstacle, meanwhile, stems from a lack of business management and administration skills, which makes financial and human resource management extremely difficult.